Kant, religion, and politics - DiCenso, James , 1957- (Cambridge University Press, 2011)
"This book offers a systematic examination of the place of religion within Kant's major writings. Kant is often thought to be highly reductionistic with regard to religion - as though religion simply provides the unsophisticated with colorful representations of moral lessons that reason alone could grasp. James DiCenso's rich and innovative discussion shows how Kant's theory of religion in fact emerges directly from his epistemology, ethics and political theory, and how it serves his larger political and ethical projects of restructuring institutions and modifying political attitudes towards greater autonomy. It also illustrates the continuing relevance of Kant's ideas for addressing issues of religion and politics that remain pressing in the contemporary world, such as just laws, transparency in the public sphere and other ethical and political concerns. The book will be valuable for a wide range of readers who are interested in Kant's thought"